Effect of Compositional Design in Ag-Cu-Based Brazing Alloys on Microstructure and Cu-STS Joining Characteristics - Lee, Chan Yang; Oh, Min Chul; Kim, Geon Hong; Ahn, Byungmin (Archives of Metallurgy and Materials, 2026)
In this study, a copper-silver-phosphorus-tin brazing filler metal with reduced silver content was designed to facilitate oxide removal and enable fluxless brazing. Based on thermodynamic phase diagram analysis, the silver and tin contents were fixed, and the influence of phosphorus content on microstructure and joint strength was investigated. Increased phosphorus content resulted in a higher fraction of copper-phosphorus intermetallic phases. The filler metal containing 65 wt.% copper, 10 wt.% silver, 5 wt.% phosphorus, and 20 wt.% tin exhibited excellent wettability and a stable interfacial microstructure at 900°C. In addition, it achieved superior joint strength compared with a commercial copper-phosphorus filler metal and showed performance comparable to that of a conventional silver-based filler metal. These results demonstrate the potential of the developed filler metal as a cost-effective solution for copper-stainless steel cooling pipe applications.